Prostate cancer imaging of FSHR antagonist modified with a hydrophilic linker. (18th August 2015) - Zhu, Chen; Xu, Qing; Pan, Donghui; Xu, Yuping; Liu, Ping; Yang, Runlin; Wang, Lizhen; Sun, Xinchen; Luo, Shineng; Yang, Min
Abstract : Follicle‐stimulating hormone receptor (FSHR) is selectively expressed in endothelial cells of prostate cancer (PCa) and becomes a potential target for tumor diagnosis and therapy. 18 F‐Al‐NOTA‐MAL‐FSH1 is a promising PET imaging probe for targeting FSHR; however, the unfavorable abdominal backgrounds may hamper clinical translation. GGGRDN is a new hydrophilic linker, which can improve the imaging quality of radiolabeled peptides. In this study, GGGRDN‐FSH1 (denoted as FSH2) was designed and conjugated with NOTA‐MAL for 18 F‐Al radiolabeling. NOTA‐MAL‐FSH2 was obtained with about 50% yield and labeled using 18 F‐Al in a one‐step method within 20 min with a yield of 41.46 ± 10.36% (non‐decay‐corrected). The radiochemical purity was more than 95% and the specific activity was more than 50 GBq/µmol. The i n vitro stability studies were determined in PBS and human serum. 18 F‐Al‐NOTA‐MAL‐FSH2 remained stable in PBS and human serum. Balb/c nude mice bearing PC‐3 human PCa were used for in vivo study. PC‐3 tumors were clearly visualized with good contrast to background through microPET. ROI analysis showed the tumor uptake values were 2.68 ± 0.52 and 1.97 ± 0.61%ID/g at 30 and 60 min post injection (p.i.), respectively. Biodistribution studies showed that the accumulations of 18 F‐Al‐NOTA‐MAL‐FSH2 in liver and intestine were 0.47 ± 0.11 and 0.12 ± 0.03%ID/g respectively at 60 min p.i. FSHR‐binding specificity was also demonstrated by reduced tumor uptake after coinjection of excessive unlabeled FSH2. In conclusion, 18 F‐Al‐NOTA‐MAL‐FSH2 was successfully prepared in a one‐step method and showed better pharmacokinetics than 18 F‐Al‐NOTA‐MAL‐FSH1. Favorable preclinical study revealed that 18 F‐Al‐NOTA‐MAL‐FSH2 appears to be a promising candidate for FSHR‐positive tumor imaging. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : GGGRDN‐modified FSH1 reduced the liver accumulation and optimized the abdominal background visualized by microPET.